Biomechanical Analysis of the Throwing Athlete and Its Impact on Return to Sport - Nicholas A. Trasolini, M.D; Kristen F. Nicholson, Ph.D; Joseph Mylott, B.S; Garrett S. Bullock, P.T., D.P.T., D.Phil; Tessa C. Hulburt, M.S; Brian R. Waterman, M.D (Elsevier, 2022)
Throwing sports remain a popular pastime and frequent source of musculoskeletal injuries, particularly those involving the shoulder and elbow. Biomechanical analyses of throwing athletes have identified pathomechanic factors that predispose throwers to injury or poor performance. These factors, or key performance indicators, are an ongoing topic of research, with the goals of improved injury prediction, prevention, and rehabilitation. Important key performance indicators in the literature to date include shoulder and elbow torque, shoulder rotation, kinetic chain function (as measured by trunk rotation timing and hip-shoulder separation), and lower-extremity mechanics (including stride characteristics). The current gold standard for biomechanical analysis of the throwing athlete involves marker-based 3-dimensional) video motion capture. Emerging technologies such as marker-less motion capture, wearable technology, and machine learning have the potential to further refine our understanding. This review will discuss the biomechanics of throwing, with particular attention to baseball pitching, while also delineating methods of modern throwing analysis, implications for clinical orthopaedic practice, and future areas of research interest. Level of Evidence: V, expert opinion.